People's Republic of China : Hong Kong Special Administrative Region; 2010 Article IV Consultation Discussions; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
Owing to prompt policy action, the Hong Kong economy is now back on a robust growth trajectory. Inflation has rebounded, driven by higher costs for utilities. Banks have withstood the financial market volatility. Higher property prices leading to higher rents and the ongoing asset price inflation will feed into higher consumer prices. Financial stability using macroprudential tools and improving the overall fiscal position will help. Preserving the flexibility and adaptability of its economy will require a careful balancing act.